The effect of eccentricity on the collapse behaviour of sandwich pipes - Fu, Guangming; Li, Mingliang; Yang, Jiankun; Sun, Baojiang; Shi, Chen; Estefen, Segen F. (Applied ocean research, 2022)
•A two-dimensional numerical model of eccentrical sandwich pipes under external pressure is developed using the finite element software ABAQUS.•Verified numerical modelling combined with a Python scripting program is employed for the parametric analysis.•The results show that eccentricity has a significant effect on the collapse of SPs. Sandwich pipes (SPs) with adequate strength performance and thermal insulation capacity have become an attractive choice for oil and gas transportation in deep water. The SP has a more complex structural configuration than the traditional single wall pipe. The fabrication process can induce eccentric behaviours of the pipe layers, influencing the external pressure resistance capacity. In this paper, a two-dimensional numerical model of eccentrical sandwich pipes under external pressure is developed using the finite element software ABAQUS. Experimental results are employed to calibrate the numerical models. The verified numerical model combined with a Python scripting program is employed to develop the parametric analysis models. The effects of geometric parameters, material properties, and interlayer friction coefficients with different eccentricities on the SP collapse behavior are investigated. The results show that eccentricity has a significant effect on the collapse of SPs. With the increase of eccentricity, the collapse pressure of SP decreases significantly. Based on the numerical simulations, the optimized design under different geometric parameters, material properties, and interlayer friction coefficients is proposed, reducing the eccentricity effect while optimizing the collapse strength of the sandwich pipe. The present results will support the design and engineering application of deepwater sandwich pipe structures.